γ-amino butyric acid (GABA) level as an overall survival risk factor in breast cancer - Anna Brzozowska; Franciszek Burdan; Dariusz Duma; Janusz Solski; Maria Mazurkiewicz (Annals of Agricultural and Environmental Medicine, 2017)
Introduction The γ-amino butyric acid (GABA) plays important role in the proliferation and migration of cancer cells. The aim of the study was to evaluate the level of GABA in breast cancer, in relation to clinical and epidemiological data.